Hubungan Kegawat Daruratan dengan Waktu Tanggap pada Pasien Jantung Koroner di RSI Siti Khadijah Palembang - Apriani, Apriani (Jurnal Kesehatan, 2017)
An emergency can be interpreted as a condition that is judged as a person's dependence on receiving medical action or immediate evaluation of the surgical action. Response time is the speed and the accuracy of service that is required by the patients to get appropriate treatment with their about diseases since entering the door of the IGD. Good response time for the patients is about 5 minutes, if it is more than it, it can make patient life’s in danger even can cause death. The aim of this study was to determine the correlation between emergency situation to response time in coronary heart disease patients at emergency room Siti Khadijah Islamic Hospital Palembang. The design of this study used an analytic observational method and cross-sectional approach, subjects of this study was the nurses of emergency room Siti Khadijah Islamic Hospital Palembang, as much as 30 respondents. The study was conducted from June 17th - July 7th, 2017. The data study was recorded on the observation sheet. Then this study data were analyzed by using chi-square test. Based on the result of data analysis by chi-square test showed that there was a significant relationship between emergency situation and response time on coronary heart disease patients and the ρ-value was 0.003 <ɑ=0.05. It can be concluded that there was a relationship between emergency situation and response time on coronary heart disease patients at emergency room Siti Khadijah Islamic Hospital Palembang.